Breaking and entering the contemporary house cut, spliced, and haunted - Elliott, Bridget 1957- (McGill-Queen's University Press, 2015)
Breaking and Entering considers how contemporary artists and filmmakers address anxieties and vulnerabilities around housing and the house by prying open both physical and metaphorical domestic structures. Deploying tactics that range from cutting into the surface of actual buildings, to making and manipulating "real" and virtual architectural models, to filming urban decay, the artists under discussion dismantle traditional domesticity to expose what remains hidden and to explore what might be salvaged and recycled. The contributors' central themes include exile and homelessness, narratives of belonging and exclusion, domestic rituals, memories, furnishing and hoarding, invasions of privacy, pleasures and perils of home ownership, utopian visions, and playing house. Broached from a variety of methodological perspectives drawn from art history, architecture, and film studies, the essays in this book invite us to contemplate what we can salvage from historical experiences of dwelling and help us find shelter in the future
Project started as as an exhibition and symposium in the ArtLab of the Department of Visual Arts at Western University
Includes bibliographical references and index
Keywords: Zuhause; Architektur; Künstler; Filmproduzent; Bedeutung; Kunst; Film; Studie; Zugehörigkeit; Aufsatzsammlung